Déguerpissements et déplacements forcé à Addis-Abeba - Bezunesh Tamru (EchoGéo)
In a predominantly liberalized economy, Addis Ababa, the Ethiopian capital city, is experiencing urban beautification and real estate development operations politically labeled “as smart city”. They all demand significant amount of land and entail the forced displacement of thousands of city dwellers. Our study focuses on the populations of the northeastern part of the capital in the Yeka forest district, and analysis the evolution of their urban citizenship. The surveys show their past urban practices between these margins and the city’s markets based on a semi-rural economy. The construction of new roads to open up these areas had benefited the inhabitants by allowing them some improvements in their living conditions. But today, the forced displacement and the destruction of their neighborhoods are not only a source of social decay, but also a challenge to their urban citizenship they had taken for granted, leading them to adopt urban survival strategies, particularly for the younger generations.